Gender disparities in music education and music-making amongst the Swedish adult population - Sam de Boise (Nordic Research in Music Education)
This article explores the extent of gender disparities in: (a) formal non-compulsory music education (FNCME), (b) instrument uptake, choice and continuation, and (c) music composition and production within the Swedish adult population. A nationally representative online survey of 1096 respondents aged 18–79 years old was conducted in 2023 and analysed using chi-squared tests and binary logistic regression. Data indicated that gender was the main factor impacting on all three aspects, intersecting significantly with age. This was even when accounting for highest level of educational attainment, employment type, personal income, region and whether respondents were born in Sweden.